Analisis Ekonomi Dalam Pembentukan Hukum (Kasus Perizinan Bisnis Ritel Modern di Sumatera Barat) - Yas Wirman; Deddi Ajir; Yusnita Eva (Risalah Iqtishadiyah, 2023)
Indonesian Modern Retail Business is a business activity selling various goods or services for direct or indirect consumption. Retail business in Indonesia can generally be classified into two, namely modern retail and traditional retail. Modern retail is actually a development of traditional retail which in practice applies modern concepts using technology and accommodates lifestyle developments in society (consumers). Modern shopping centers currently operating in West Sumatra include Plaza Andalas, Basko Grand Mall, Rocky Plaza, Transmart and SPR Plaza. To protect micro, small and medium enterprises (MSMEs), the West Sumatra Government also does not give permits to franchise retail networks in the form of minimarkets such as Indomaret and Alfamart which have mushroomed in various cities in Indonesia. Instead, the Minang Mart minimarket network was formed by the Regional Owned Enterprise (BUMD) PT Graphics Jaya West Sumatra in collaboration with PT Sentra Distribution Nusantara.